z = ( 2 1 2 + 2 + 2 + 2 i 2 − 2 + 2 ) 4
Calculate the exact value of 1 0 0 ∣ z ∣ , rounded to the nearest hundredths place.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
By the double angle formulas, used to derive the half angle formulas, the following can be obtained: 2 1 2 + 2 + 2 = cos 1 6 π and 2 i 2 − 2 + 2 = sin 1 6 π By DeMoivre's formula, we obtain
( cos 1 6 π + i sin 1 6 π ) 4 = cos 4 π + i sin 4 π
whereof the norm is easily seen to be 1 , so the final answer is 1 0 0 . 0 0 .
DeMoivre's formula may look almost too good to be true, but if you write complex numbers in their polar form and use e i θ = cos θ + i sin θ , the additivity of exponents shows that if a , b ∈ C , then ar g a b = ar g a + ar g b . In other words, multiplication of complex numbers a and b rotates 1 by ar g a + ar g b and scales 1 by ∣ a b ∣ .
z = ( 2 1 2 + 2 + 2 + 2 i 2 − 2 + 2 ) 4 = 2 4 1 ( 2 + 2 + 2 + i 2 − 2 + 2 ) 4 = 2 4 1 ( ∣ ∣ ∣ ∣ ∣ 2 + 2 + 2 + i 2 − 2 + 2 ∣ ∣ ∣ ∣ ∣ e ar g ( 2 + 2 + 2 + i 2 − 2 + 2 ) ) 4 = 2 4 1 ( 2 + 2 + 2 + 2 − 2 + 2 e ar g ( 2 + 2 + 2 + i 2 − 2 + 2 ) ) 4 = 2 4 1 ( 4 e ar g ( 2 + 2 + 2 + i 2 − 2 + 2 ) ) 4 = 2 4 2 4 e 4 ar g ( 2 + 2 + 2 + i 2 − 2 + 2 ) = e 4 ar g ( 2 + 2 + 2 + i 2 − 2 + 2 )
Therefore ∣ z ∣ = 1 and 1 0 0 ∣ z ∣ = 1 0 0 . 0 0
If we believe this problem has a nice solution, we may hope to be able to write
cos θ = 2 1 2 + 2 + 2 ,
for some θ ∈ [ 0 , 2 π ) . If that is the case, observe that using the identity we can find the value of the corresponding sine. That'll yield
sin θ = 2 1 2 − 2 + 2 ,
which is exactly the imaginary part of a number z 1 / 4 . In this case, we can write our number as
z = ( cos θ + i sin θ ) 4 = e 4 i θ ,
which has modulus 1 .
Problem Loading...
Note Loading...
Set Loading...
If we write x = 2 1 2 + 2 + 2 y = 2 1 2 − 2 + 2 then x 2 + y 2 = 4 1 [ 2 + 2 + 2 + 2 − 2 + 2 ] = 1 so that z = ( x + i y ) 4 clearly has modulus 1 , making the answer 1 0 0 .